2020
DOI: 10.4314/ahs.v20i3.39
|View full text |Cite
|
Sign up to set email alerts
|

Weight reduction ameliorates inflammatory cytokines, adipocytokines and endothelial dysfunction biomarkers among Saudi patients with type 2 diabetes

Abstract: Background: Type 2 diabetes mellitus (T2DM) considered as one of the cardiovascular disorders (CVD) principle risk fac- tor as diabetes is associated with abnormal levels of endothelial function, inflammatory and adipocytokines. Objective: The aim of this study was to measure the impact of weight reducing on inflammatory cytokines, adipocytokines and endothelial function biomarkers among obese T2DM patients. Methods: One–hundred T2DM patients enrolled in the present study; the age range was 35-55 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…The complete text of the remaining 29 articles was evaluated, and among them, 14 articles were excluded due to their lack of CG (control group) or CG not engaging in exercise, as well as ambiguous or incomplete data. Therefore, 15 records were included in this study; however, two records [23,24] were the subsequent study of Abd El-Kader, Al-Jiffri [25] and thus, Abd El-Kader, Al-Jiffri [25] was used as the reference record in this review. While Abd El-Kader and Al-Jiffri [24] reported data on leptin and adiponectin, Osama and Shehab [23] reported on lipid pro les.…”
Section: Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete text of the remaining 29 articles was evaluated, and among them, 14 articles were excluded due to their lack of CG (control group) or CG not engaging in exercise, as well as ambiguous or incomplete data. Therefore, 15 records were included in this study; however, two records [23,24] were the subsequent study of Abd El-Kader, Al-Jiffri [25] and thus, Abd El-Kader, Al-Jiffri [25] was used as the reference record in this review. While Abd El-Kader and Al-Jiffri [24] reported data on leptin and adiponectin, Osama and Shehab [23] reported on lipid pro les.…”
Section: Searchmentioning
confidence: 99%
“…In the included trials, patients were randomly allocated to intervention and CG. In all 13 trials, the intervention of AEDT [25][26][27][28][29][30][31][32][33][34][35][36][37]. The duration of the interventions in the included trials was varied.…”
Section: The Intervention Characteristicsmentioning
confidence: 99%
“…Additionally, clinical studies have reported an anti-inflammatory, cardioprotective and slimming effect of PA. For example, a study in obese men showed that exercise was more effective than diet in reducing body weight (BW), improving the systemic inflammatory profile and IR and circulating levels of adipokines ( 204 ). Likewise, a study conducted in obese patients with T2DM subjected to dietary restriction and aerobic exercise reported that after a 3-month intervention, adiponectin levels rose while BMI and TNF-α, IL-6 and leptin levels fell significantly ( 205 ).…”
Section: Non-pharmacological Approach To Adipocyte-myocardiocyte Defective Signaling: Impact Of Lifestylementioning
confidence: 99%
“…Saudi scientists 38 describe how “weight reduction ameliorates inflammatory cytokines, adipocytokines and endothelial dysfunction biomarkers among patients with type 2 diabetes.”…”
Section: Now To Diabetes Mellitusmentioning
confidence: 99%